The effect of planned behavior theory-based education on computer game dependence in high school male students - Hassan Zamanian; Gholamreza Sharifzadeh; Mitra Moodi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Teenagers are increasingly interested in computer games, and the adverse effects of these games are dependent on the execution of these games. The theory of planned behavior (TPB) is one of the most important theories in behavior change. This study aimed to determine the effect of educational planning based on TPB on the level of dependence on computer games in high school male students in Gonabad, Iran. MATERIALS AND METHODS: This was a randomized controlled trial. The study population was students of computer games in Gonabad. Sixty-four students were selected by a multistage random sampling method and were randomly divided into intervention (n = 32) and control (n = 32) groups. Data-gathering tool was the standard questionnaire of computer game dependency and researcher-made questionnaire according to TPB constructs that were completed before, immediately, and 3 months after the intervention. The intervention consisted of eight 90-min training sessions. Data were analyzed using the Chi-square test, Fisher's, t-test, repeated measures ANOVA, and Bonferroni post hoc test. RESULTS: Before the intervention, the intervention and control groups were matched for the mean score of model constructs. However, after the intervention, the mean score of computer game addiction significantly decreased (≤0.001). However, the mean score of knowledge, attitude, perceived behavioral control, and behavioral intention increased, which was statistically significant. Furthermore, the mean changes of model structures were statistically significant (P < 0.05). CONCLUSION: The findings revealed that TPB can be used as a good theoretical framework for designing and implementing educational programs to reduce the dependency of computer games on students.